Large Population and Unhygienic Conditions are “Blessings in Disguise” Amid Asian Countries for Low Infection Rate of COVID-19 as Compared to Europe and America - Khan, MD, PhD, Muhammad Mujahid; Khan, MD, M.Phil, Sadia Wazir; Khan, MD, PhD, Mohammed Moizuddin; Altamimi, MD, PhD, Tahani Nasser; Khan, MD, Shifa; Alnajashi, Saleh Sulaiman; Al-Ameer, Mahdi; Alanazi, Meshari Talal; Al-Hamidi, PhD, Abdulaziz (International Journal of Innovative Research in Medical Science, 2021)
This epidemiological cross-sectional data-based study aimed to explore the morbidity and mortality patterns of novel coronavirus infections (COVID-19) among the worst affected regions of the world. The data on the worldwide pandemic of COVID-19 were obtained from World Health Organization (WHO), John Hopkin’s University research center, Worldometer, Centers for Disease Control and Prevention (CDC), since its outbreak until August 5, 2020. The evidences were also recorded from research papers published in international scientific journals indexed in Pub Med and Institute of Scientific Information (ISI) Web of Science. The findings show that the average of COVID-19 cases in Europe is 154754 cases per million of the population, in America (both north and south) is 47982 cases per million of the population and in Asia is 13280 cases per million of the population. The mean value of mortality rate in Europe, America (both north and south) and Asia is 2436 deaths per million of population, 2158 deaths per million of population, and 181 deaths per million people, respectively. The study broadly concludes that the infection rate and mortality are higher in developed countries than in developing or underdeveloped countries. The perceptible causes of increase in infection rate and mortality in developed European and American countries may be the difference in individual and herd immunity in the population due to less exposure to similar viruses. The lack of exposure may be attributed to better economic conditions leading to relatively good hygienic practices as compared to the developing and underdeveloped countries of the Asian region.